TRIANGLE LOVE OF BELLA SWAN IN CHRIS WEITZ'S NEW MOON (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Citraningrum, Ayu Anggit (2011)
The major problem of this study is how triangle love of Bella Swan reflected in the major character's personality. The objective of the study is to analyze the movie based on structural elements and to analyze triangle love of Bella Swan based on an individual psychological approach. This study focuses on the major character, namely Bella. The benefit of this study is to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the movie itself, New Moon by Chris Weitz, while the secondary data taken from some information needed. The method of data collection is qualitative method. Based on the analysis, the writer concludes that struggle for love of Bella Swan in New Moon film is influenced by some aspect. They are fictional finalism, inferiority feeling, striving for superiority, style of life, social interest and creative power. The six elements above have closed relationship. Bella swan has goal to find her love, Edward Cullen. She has to control her inferiority feeling that she might be old and Edward can't. She is striving for superiority, has a useful social type, low social interest and she has creative power. All of six elements above are needed for Bella for getting her goal. Based on An Individual Psychological aspects shown in the film, the writer then concludes that literary work reflects the condition of people who has a dream or goal and they struggle to get it.